2008
DOI: 10.1152/ajpheart.00127.2008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure-function relationship of elastin and its impact on the proximal pulmonary arterial mechanics of hypertensive calves

Abstract: Extracellular matrix remodeling has been proposed as one mechanism by which proximal pulmonary arteries stiffen during pulmonary arterial hypertension (PAH). Although some attention has been paid to the role of collagen and metallomatrix proteins in affecting vascular stiffness, much less work has been performed on changes in elastin structure-function relationships in PAH. Such work is warranted, given the importance of elastin as the structural protein primarily responsible for the passive elastic behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
162
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(178 citation statements)
references
References 47 publications
15
162
0
1
Order By: Relevance
“…27 This allows for the tissue to move freely in both directions, circumferential and longitudinal. The strain was measured optically by software that keeps track of the relative distance between the black dots on the sample (optical markers).…”
Section: Western Immunoblotmentioning
confidence: 99%
“…27 This allows for the tissue to move freely in both directions, circumferential and longitudinal. The strain was measured optically by software that keeps track of the relative distance between the black dots on the sample (optical markers).…”
Section: Western Immunoblotmentioning
confidence: 99%
“…biomechanics; mechanobiology; elastin; hydroxyproline; recovery HYPOXIC PULMONARY HYPERTENSION (HPH) is caused by living at high altitudes and is a complication of many lung diseases, including chronic obstructive pulmonary disease (1, 13, 16), cystic fibrosis (10), and obstructive sleep apnea (13), which contributes significantly to morbidity and mortality. Pulmonary vascular remodeling due to chronic HPH increases conduit pulmonary artery (PA) stiffness (4,20,21,23,34,42). Conduit PA stiffening likely increases wave reflections to impair right ventricular systolic function, much like aortic stiffening impairs left ventricular systolic function (18,29,33).…”
mentioning
confidence: 99%
“…Our laboratory has previously shown that HPH increases wave reflections in the mouse pulmonary circulation (44). Recent evidence showing that conduit PA stiffness is a strong predictor of mortality in PA hypertension (12, 30) further supports the importance of PA stiffness to pulmonary and right ventricular function.The dominant morphological changes in conduit PAs in response to HPH are accumulation of collagen and elastin (20, 21) and wall thickening (4,20,21,23). Stiffening of the extralobar PAs has been shown to be linked with accumulation of collagen and elastin (4,20,21,23,42).…”
mentioning
confidence: 99%
See 2 more Smart Citations